Reparación de la transmisión automática y afinación del motor de un vehículo dodge dakota del año 1995 - Monserrate Patiño, Denis Oliver (2014)
This paper describes step by step how held REPAIR AUTOMATIC TRANSMISSION AND TUNING MOTOR VEHICLE DODGE DAKOTA 1995 The main objective of the project is to repair the automatic transmission, but it is necessary to tune the engine for then check the actual state of the case. When you mention tuning the engine some think only maintenance is performed but it should be emphasized that the engine had some significant flaws and that correction was necessary; to carry out it was put into practice knowledge acquired in college and with the help of manual and painstaking research the various engine problems were resolved . Once the engine tuning was completed it was found the actual state of automatic transmission and the diagnosis, transmission has its roots even before it had been repaired but was not a success, because of this the car passed without work near one year. Overall , this project some considerable problems were corrected and is not only limited to repair by replacing a part with a new one , but the analysis of the causes that produced damage , so bring a final solution to all problems.